Murabahah finance as a potential moderator on the relationship between farm infrastructure and agricultural output in Kano State, Nigeria: a propose frame work - Mohammed, Ahmed Ibrahim; Bashir, Ahmad; Ogunbado, Ahamad Faosiy; Adamu, Sani; Salisu, Yahuza; Yakubu, Surajo Musa (2016)
Agriculture is act of soil cultivation, rearing of animals, forestry for the purpose of food supply and raw material to the industries for human satisfaction and poverty eradication as well as economic growth.However, the agricultural output in Kano state is declining day after day. Despite the socioeconomic importance of agriculture and the initiatives of both public and private organizations to grow the output, yet the problem is increasing. The objective of this paper is to propose a model for examining the moderating influence of Murabahah finance on the relationship between farm infrastructure and agricultural output in Kano State Nigeria.The study proposes a model that hopes to use by the Kano state ministry of agriculture, financial institutions and farmer cooperatives to the tackle the problems.In addition, this paper introduces Murabahah finance as a potential moderating variable.